Ultra-Broadband Dielectric and Optical Kerr-Effect Study of the Ionic Liquids Ethyl and Propylammonium Nitrate - Sonnleitner, Thomas; Turton, David A; Hefter, Glenn; Ortner, Alexander; Waselikowski, Stefan; Walther, Markus; Wynne, Klaas; Buchner, Richard (The journal of physical chemistry. B, 2015)
Dielectric relaxation (DR) and optical Kerr-effect (OKE) spectra of the archetypal protic ionic liquids ethyl- and propylammonium nitrate (EAN and PAN) have been measured over an unusually large frequency range from 200 MHz to 10 THz at temperatures (mostly) between 5 and 65 °C. Analysis of the low-frequency α-relaxation, associated with the cooperative relaxations of the cations (DR) and anions (OKE) and any clusters present, indicated that ion reorientation in EAN is decoupled from viscosity and occurs via cooperative relaxation involving large-angle jumps rather than rotational diffusion. Detailed consideration of the high-frequency parts of the DR and OKE spectra showed that the observed intensities were a complex combination of overlapping and possibly coupled modes. In addition to previously identified intermolecular H-bond vibrations, there are significant contributions from the librations of the cations and anions. The present assignments were shown to be consistent with the isotopic shifts observed for deuterated EAN.